Edukasi kesehatan tentang status vaksinasi dengan kejadian stunting - Yulianto, Andri; Yusnita, Yusnita (JOURNAL OF Public Health Concerns, 2022)
Introduction: Stunting conditions at birth affect the development or growth of children so that stunting toddlers in the future will have difficulty in achieving optimal physical and cognitive development. Objective: To determine the relationship between vaccination status and the incidence of stunting. Methods: Analytical observational research with a case-control study approach. The sampling technique used is simple random sampling with a sample size of 99 respondents. Collecting data using observation sheets and MCH handbooks. statistical analysis using Chi Square Statistical Test. Results: From 33 toddlers 1-3 years old, there were 19 (57.6%) respondents who experienced stunting with a history of vaccination status in the incomplete category and 14 (42.4%) complete respondents. there is a relationship between vaccination status and the incidence of stunting in infants aged 1-3 years, the P value is 0.011 (smaller than alpha = 0.05). Conclusion: There is a relationship between vaccination status and the incidence of stunting in infants aged 1-3 years in the Work Area of ​​the Wates Health Center.   Pendahuluan: Kondisi stunting saat lahir berpengaruh terhadap perkembangan atau pertumbuhan anak sehingga balita stunting di masa dating akan mengalami kesulitan dalam mencapai perkembangan fisik dan kognitif yang optimal. Tujuan: Untuk mengetahui hubungan status vaksinasi dengan kejadian stunting. Metode: Penelitian observasional analitik dengan penekatan  studi kasus control. Teknik sampling yang digunakan yaitu simple random sampling dengan jumlah sampel yaitu 99 responden. Pengumpulan data menggunakan lembar observasi dan buku KIA. analisis stastistik mengunakan Uji Statistik Chi Square. Hasil: Diketahui dari 33 balita 1-3 tahun didapatkan yang mengalami stunting dengan riwayat status vaksinasi dalam kategori tidak lengkap sebanyak 19 (57,6%) responden dan lengkap 14 (42,4%) responden. ada hubungan status vaksinasi terhadap kejadian stunting pada bayi usia 1-3 tahun  diperoleh nilai P sebesar 0,011 (Lebih kecil dari nilai alpha = 0,05). Simpulan: Ada hubungan status vaksinasi terhadap kejadian stunting pada bayi usia 1-3 tahun  di wilayah kerja Puskesmas Wates.